Políticas editoriales e impacto cultural en la Argentina (1880-2000) - Aguado, Amelia (2006)
En el proyecto de investigación reseñado, se estudia la evolución de la industria editorial en Argentina, desde 1880 a 2000, y se analiza su impacto cultural, con particular énfasis en la literatura argentina.
In the research project reviewed, the evolution of the edition industry in Argentine, from 1880 to 2000, is studied and its cultural impact is analyzed, with particular enphasis in Argentine literature.
Keywords: Industria Editorial; Argentina; 1880-2000; Literatura argentina; Edition industry; Argentine literature; 1880-2000; Argentina